Administration of chloroquine or hydroxychloroquine through feeding tubes: new challenges in times of coronavirus pandemic - Mariana Martins Gonzaga do Nascimento; Sandra Regina Santos; Cristiane de Paula Rezende; Raquel Linhares Bello de Araújo (São Paulo State University (UNESP), 2020)
The use of chloroquine and hydroxychloroquine as off-label treatments for covid-19 disease is a resort for critical care patients under enteral nutrition (EN). However, the use of solid pharmaceutical forms of these drugs through feeding tubes can pose a challenge to the health care team. Therefore, we performed a review of literature regarding administration of chloroquine and hydroxychloroquine through feeding tubes. For this end, a search was performed on PubMed and Lilacs database using key-words and free terms referring to drug administration via feeding tubes, and, specifically chloroquine and hydroxychloroquine. Also, a search on Micromedex® database and on the Handbook of Drug Administration via Enteral Feeding Tubes were performed. A total of 1.784 articles were retrieved. However, 4 articles fitted in the inclusion criteria. Two articles exploring the administration of chloroquine via feeding tubes on children with malaria found no difference on clinical results or tolerability when comparing it with oral or intramuscular administration. Other article showed full dispersion of hydroxychloroquine on water after crushing with mortar and pestle. A review found no information regarding the administration of hydroxychloroquine via postpyloric feeding tubes. No information was found on Micromedex® or the consulted Handbook; however, they pointed out the interaction between chloroquine and multivalent ions if coadministered.